Apport De L’étude Géotechnique, Minéralogique Et Géochimique Pour La Valorisation Des Carrières De Sable De La Région De Meknès (Maroc) - Benbaqqal, Hicham; Masrour, Aissa; Mahjoubi, Rachida; Benyassine, El Mehdi; Erragragui, Mohamed; Gretaa, Mostafa (European Scientific Journal, ESJ, 2017)
The plateau of Meknes and its borders shows a great geological diversity. The plateau is formed by a cover of marls, fawn sands and lacustrine limestones. The geological formations of the borders are composed of dolomitic limestones and marls of Jurassic age. The quarries of the plateau of Meknes and its borders are of diversified geological nature. In this region, the problem of increased demand for building materials causes excessive overexploitation, without taking account of quality and rational use measures. This problem requires a study of the state of the quality of these materials to guide the entrepreneurs towards the places where the quarries are of quality required by the standards of the field of the BTP, and on the other hand to control over the abuse user of these building materials and its influence on the environment. For these aims, a study of mineralogical and chemical analyzes by X-ray diffraction and by ICP-AES was carried on the samples taken from four quarries of materials used in this region. Thus, the physical and mechanical parameters of the materials are measured according to the most fundamental geotechnical protocols in the construction geomaterials. These analytical results have allowed to class spatially of the mineralogical, geochemical and geotechnical quality of this material in comparison with the standards.